Study guides

☆☆

Q: Factorise x squared plus 13x plus 42?

Write your answer...

Submit

Related questions

42 + x2 = 13x ∴ x2 - 13x + 42 = 0 ∴ (x - 6)(x - 7) = 0 ∴ x ∈ {6, 7}

This is a quadratic equation question which will have two answers: 2x2+42 = x2+13x 2x2-x2-13x+42 = 0 x2-13x+42 = 0 Factorising the equation gives you: (x-6)(x-7) = 0 Therefore: x = 6 or x = 7

The expression cannot be factorised.

2x - 13x + 42 = x +ax + b a + b = 2(x - 6.5x + 21) = 34 = a + b

3060.

7x2+49x-42 = 7(x2+7x-6)

(x - 6)(x - 7)

42 squared - or 42 x 42 is 1764

t2+ t - 42 it can't be simplified anymore

2752 = 75625 42 = 16 32 = 9 22 = 4 75625/16 + 9 + 2 = 4737.5625

They are 81+16 = 9792 + 42 = 97nine squared plus four squared

(x - 6)(x - 7)

They are equal. 7 squared is 7 x 7, which equals 49. 6 x 7 = 42, plus another 7 = 49.

It is a quadratic expession and when factored is: (x-6)(x+7).

42

Answer: 42 m² = 452.084 ft²

x3 + 13x2 + 42x = x(x2 + 13x + 42) = x(x2 + 6x + 7x + 42) = x[x(x + 6) + 7(x + 6)] = x(x + 7)(x + 6)

x = ? 42 = x squared minus x

Well, it really depends on Y. For say, if Y=3 the answer is 42.

-42 = 16

6.4807407

44

x2 + 13x + 4 = (x + 6½ + √38¼)(x + 6½ - √38¼). To find this, we need to find p and q, where p + q = 13, pq = 4. 4 = 42¼ - 38¼ = (6½ + √38¼)(6½ - √38¼); thus, p = (6½ + √38¼), q = (6½ - √38¼).

6x3+29x2-40x-42 divided by 6x+5 Quotient: x2+4x-10 Remainder: 8

42=4x4=16.